2014
DOI: 10.1002/ebch.1976
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for prevention of necrotizing enterocolitis in preterm infants

Abstract: Probiotics for prevention of necrotizing enterocolitis in preterm infants Necrotizing enterocolitis (NEC) is a serious disease that affects the bowel of premature infants in the first few weeks of life. Although the cause of NEC is not entirely known, milk feeding and bacterial growth play a role. Probiotics (dietary supplements containing potentially beneficial bacteria or yeast) have been used to prevent NEC. Our review of studies found that the use of probiotics reduces the occurrence of NEC and death in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
6
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 67 publications
4
181
6
6
Order By: Relevance
“…In light of these limitations, the current approach to deal with this threat is treating the symptoms as they appear and trying different approaches for prevention such as providing probiotics or feeding the preterm infant with HBM (21). While some studies have been performed in the field of probiotics and their effect on NEC (1,22), fewer studies have been conducted on the effect of HBM on NEC and even less is known about the mechanisms by which HBM components can contribute to the protective effect of HBM on NEC.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these limitations, the current approach to deal with this threat is treating the symptoms as they appear and trying different approaches for prevention such as providing probiotics or feeding the preterm infant with HBM (21). While some studies have been performed in the field of probiotics and their effect on NEC (1,22), fewer studies have been conducted on the effect of HBM on NEC and even less is known about the mechanisms by which HBM components can contribute to the protective effect of HBM on NEC.…”
Section: Discussionmentioning
confidence: 99%
“…One option is manipulation of the microbiota, an approach well illustrated by the successes reported for probiotics. In a meta-analysis that examined over 5000 neonates, probiotics reduced severe NEC and all-cause mortality [9]. Approaches using complex microbial communities to restore damaged microbial ecosystems (effective at curing other diseases characterized by dysbiosis, such as recurrent C. difficile infection) are also intriguing, but have not been investigated in the preterm infant population [10].…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, probiotics potentially compete with other organisms for binding sites and substrate in the bowel. 49,50 Microbiota disturbances early in HIV infection lead to greater dominance of potential pathogens, reduced levels of Bifidobacteria and Lactobacillus spp. and increasing mucosal inflammation.…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…53 Randomised controlled trials that used a multistrain probiotic reported a significant decline in NEC, whereas those reporting a lesser decline used a single organism, such as L. rhamnosus GG. 49,53,54 …”
Section: Necrotising Enterocolitismentioning
confidence: 99%